Three-dimensional spatiotemporal imaging correlation in the diagnosis of isolated infracardiac total anomalous pulmonary venous connection in fetal life - Mani Ram Krishna; Usha Nandhini Sennaiyan (Wolters Kluwer Medknow Publications, 2023)
Total anomalous pulmonary venous connection (TAPVC) is a critical congenital heart disease which is often missed on prenatal echocardiography because of the decreased pulmonary blood flow in fetal life. Improvement in technology has resulted in increasing prenatal diagnosis of this condition. We report a foetus with infra cardiac TAPVC in whom prenatal diagnosis was facilitated by the use of STIC technology.